TUTURAN MASYARAKAT BENTENG SOMBA OPU (KAJIAN SOSIOLINGUISTIK) - Suga Hutami; Muhammad Rapi; Idawati Garim (Wahana Literasi: Journal of Language, Literature, and Linguistics, 2022)
The purpose of this study is to describe the variety and use of the speech of the people of Fort Somba Opu. The research method used is descriptive qualitative. The data of this research is the oral speech of the people of Fort Somba Opu. The source of data in this study is the people of Fort Somba Opu. Data collection techniques, namely observation and recording techniques. Data analysis techniques were carried out through raw data collection, data transcription, data identification, data classification, data analysis, and result description. The results of this study indicate that there are variations in Indonesian speech in the Makassar dialect used by speakers to the interlocutor marked by the markers –mi, iyo, and tong as a form of familiarity. Furthermore, eight aspects of SPEAKING were found in the use of speech, namely the setting and scene that took place in a school with a bustling atmosphere before breaking the fast together, there were four teachers and several students participating, using a glass of mineral water to fill with fruit ice, act sequences of conversation in the form of a question. answer with the contents of the conversation talking about the glass for fruit ice, the key (way, tone, and attitude) of speech is uttered briefly, clearly with high intonation, instrumentalities with spoken language, norms according to speech ethics even though the teacher's tone speaks firmly, and genres of speech usually in the form of a question.